A proteção de dados pessoais em banco de dados públicos no atual contexto da sociedade da informação: reflexões sobre o tratamento de dados pessoais pelo poder público brasileiro - Macedo, Nathália Brito de (2022)
This research brings explanations about the personal data protection in public database. Through the first chapter, the importance of the personal data protection in the information society is contextualized. Approaches about development of information and knowledge technologies and the internet’s importance for communication networks development. From that, investigate about the importance of personal data in the Informational Revolution’s context. Demonstrate the increase of processing capacity from this data with technological innovations like big data, data mining, artificial intelligence, among others. Approaches about the importance of information technologies and new data processing Technologies for principles of Public Administration achievement. Brings considerations about the protection of personal data and possible conflicts with the concept of open data and digital democracy in the context of the sharing economy. It develops the concept of surveillance capitalism and introduces reflections about the role of personal data for the exercise of citizenship and democracy. The second chapter approaches about the fundamental rights involved in personal data protection. Discusses the doctrinal and jurisprudential understanding of the construction of the right to the protection of personal data. It investigates the fundamental rights related to the subject of data protection, such as the right to privacy, the free development of the personality, the rights of freedom and informational self-determination. It emphasizes the importance of the autonomous normative construction of the right to the protection of personal data in the context of the information society. It addresses the right to the protection of personal data’s fundamentality and its jurisprudential conceptualization when analyzing the decisions of the Federal Supreme Court on the subject. It introduces the study of the Brazilian personal data protection microsystem with the advent of the General Personal Data Protection Law and other legislation that already dealt with data protection and privacy. Introduces the study of the protection of personal data within the scope of the Public Power. It starts an investigation about the compatibility between the principles of Public Administration and the principles relating to the protection of personal data. It discusses the importance of compatibility between the administrative legal regime and the laws that bind the Public Power with the laws that deal with the protection of personal data, such as the LAI and the LGPD. Defines the legal bases for the processing of personal data by the Public Power when investigating the legal regime for the processing of personal data both in the LGPD and in other laws.